1978
DOI: 10.1080/00039896.1978.10667318
|View full text |Cite
|
Sign up to set email alerts
|

Radioactive Mercury Distribution in Biological Fluids and Excretion in Human Subjects after Inhalation of Mercury Vapor

Abstract: The distribution of mercury in red blood cells (RBCs) and plasma, and its excretion in urine and feces are described in five human subjects during the first 7 days following inhalation of radioactive mercury vapor. A major portion (98%) of radioactive mercury in whole blood is initially accumulated in the RBCs and is transferred partly to the plasma compartment until the ratio of mercury in RBCs to plasma is about 2 within 20 hr. The cumulative urinary and fecal excretion of mercury for 7 days is about 11.6% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0
2

Year Published

1981
1981
2007
2007

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 131 publications
(50 citation statements)
references
References 5 publications
0
48
0
2
Order By: Relevance
“…In the stud y by Nakaaki et al (10), inorganic mercur y taken up in the body was excreted rather slowly; an increase in urinary excretion became evident after 10 d of exposure at 40-60 j.lg /m ' . Cherian et al (2) also found that mercury is pooled in the kidney before entering the urine, and the biological half-time for mercury loss from the kidney is approximately 64 d. As numerous investigators have already noted, urinary concentrations of inorganic mercury would tend to reflect levels of chronic exposure , perhaps kidney accumulation of mercury, rather than those of recent exposure. It appears therefore that the urinary excretion of elemental mercury is faster than that of inorganic mercury and, moreo ver, can be expected to reflect the levels of individual exposure on that same day.…”
Section: Discussionmentioning
confidence: 98%
“…In the stud y by Nakaaki et al (10), inorganic mercur y taken up in the body was excreted rather slowly; an increase in urinary excretion became evident after 10 d of exposure at 40-60 j.lg /m ' . Cherian et al (2) also found that mercury is pooled in the kidney before entering the urine, and the biological half-time for mercury loss from the kidney is approximately 64 d. As numerous investigators have already noted, urinary concentrations of inorganic mercury would tend to reflect levels of chronic exposure , perhaps kidney accumulation of mercury, rather than those of recent exposure. It appears therefore that the urinary excretion of elemental mercury is faster than that of inorganic mercury and, moreo ver, can be expected to reflect the levels of individual exposure on that same day.…”
Section: Discussionmentioning
confidence: 98%
“…22 This circulating mercury is partitioned between packed cells and plasma. 23 Improvement of technical equipment and better standards of hygiene, however, can reduce exposure significantly. The way in which amalgam is prepared, cleaning habits, and types of floor coverings have been pointed out to be important factors.…”
Section: Discussionmentioning
confidence: 99%
“…before the steady state has been reached, has not been extensively described in the literature. At least 50% of the mercury in the blood compartment is cleared with a half life of about three days (2). Blood, therefore, probably indicates recent exposure.…”
Section: Introductionmentioning
confidence: 99%